DIVERSIFICATION OF PROCESSING AND UNTILIZATION OF TUNA SKIN THUNNUS SP. IN DENPASAR BALI - Dewi, Niswa Kamila; Farida, Iftachul (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Fishery products are perishable foodstuffs, requiring proper handling to maintain their quality until they reach consumers. The application of fishery processing technology plays a crucial role in extending shelf life, maintaining quality, and supporting food diversication efforts. Furthermore, these technological developments have a positive impact on improving the welfare and income of communities dependent on the fisheries sector. Diversifying processed fish products is one way to demonstrate to the public that fish can be enjoyed not only fried, grilled, or cooked whole, but also into a varienty of more attractive, modern, and nutritious dishes. Overall, processing and diversification of fishery products is a crucial strategy for increasing added value, expanding markets, and supporting the sustainability of fisheries businesses.